(untitled) (Journal of Engineering, 2010)
The fatigue damage is a dangerous and could be considered as the most unwanted failure in the materials that are used to construct the engineering components. As composites take an advanced position in the industry of aircraft, marine and many other high performance components, because of their high ability and their light weight and for their strength, this forces us to find the deformation and data to give a good expectation for the composite behavior under fatigue and other types of damage. In this study the material used is the glass fiber with a polyester resin; the experiment used a device to force the composite to be under a bending fatigue through specified deflection and then the force is measured. The results for different values of imposed deflection and different thicknesses are presented, as S-N curves and in a logarithmic way.nFractography has been used to characterize the fatigue damage in the composite, it is shown that the fatigue damage in the composite is a complex, interactive damage process and combines between several damage mechanisms such as delamination, fiber breakage, matrix cracking and fiber matrix debounding.